Grammatical Class Effects Across Impaired Child and Adult Populations - Kambanaros, Maria; Grohmann, Kleanthes K. (Frontiers in Psychology, 2015)
The aims of this study are to compare quantitative and qualitative differences for noun/verb retrieval across language-impaired groups, examine naming errors with reference to psycholinguistic models of word processing, and shed light on the nature of the naming deficit as well as determine relevant group commonalities and differences. This includes an attempt to establish whether error types differentiate language-impaired children from adults, to determine effects of psycholinguistic variables on naming accuracies, and to link the results to genetic mechanisms and/or neural circuitry in the brain. A total of 89 (language-)impaired participants took part in this report: 24 adults with acquired aphasia, 20 adults with schizophrenia-spectrum disorder, 31 adults with relapsing-remitting multiple sclerosis, and 14 children with specific language impairment. The results of simultaneous multiple regression analyses for the errors in verb naming compared to the psycholinguistic variables for all language-impaired groups are reported and discussed in relation to models of lexical processing. This discussion will lead to considerations of genetic and/or neurobiological underpinnings: (1) Presence of the noun–verb dissociation in focal and non-focal brain impairment make localization theories redundant, but support for wider neural network involvement. (2) The patterns reported cannot be reduced to any one level of language processing, suggesting multiple interactions at different levels (e.g., receptive vs. expressive language abilities). (3) Semantic-conceptual properties constrain syntactic properties with implications for phonological word form retrieval. (4) Competition needs to be resolved at both conceptual and phonological levels of representation. Moreover, this study may provide a cross-pathological baseline that can be probed further with respect to recent suggestions concerning a reconsideration of open- vs. closed-class items, according to which verbs may actually fall into the latter rather than the standardly received former class.